(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The use of fallacious rhetoric in a bid to cajole gullible electorate is not unexpected as the 2023 presidential elections draw near. Consequently, this paper dubbed “A Critical Discourse Analysis of Peter Obi’s Acceptance Speech as Labour Party’s (LP) Presidential Candidate’ examines the use of language in political discourse. Norman Fairclough’s Relational-Dialectic Model which is rooted in Critical Discourse Analysis is the theoretical framework. It considers political discourse as three dimensional: texts (the objects of linguistic analysis), discursive practices (the production distribution and consumption of texts) and social practice (the power relations, ideologies as hegemonic struggles that discourses reproduce, challenge or restructure). This model is deployed to find out the formal features of Peter Gregory Obi’s speech in relation to language, power and ideology. The methodology involves word usage analysis, mostly personal pronouns, frequency of positive and negative words, the use of ideologies in the speech and Greek mythology. Based on these premises, certain excerpts from the text are first highlighted and then analyzed based in line with the viewpoints mentioned above. Having said this, findings in this paper reveal that the most dominant personal pronouns are “Our”, “I” and “We” which separately accounted for 29%, 19% and 19% respectively, showing that the LP Presidential candidate is calling more for collective responsibility than individual responsibility. Similarly, there were both negative and positive adjectives in the speech. The former accounted for 56.3% while the latter accounted for 41.7%. The descriptive adjectives were used to give more information and detail to both the political state of things and the heightened nature of negative politicking in Nigeria. The dominance of negative adjectives show that things have really gone from bad to worse because of the worsening cases of unwanted but entrenched capitalism while the positive adjectives tell the reader to wake up and fight for their country like the Greeks using their voters card in the coming elections. On the whole, it is concluded that the speech is typical of most political speeches mostly in terms of tone and approach; however, it is assumed, in the context of this paper, that there is a possibility that this speech addressed issues rather than attacked individuals. This is the gap this paper tries to fill; and therefore, it makes a case for issue-based campaigns going into the forthcoming elections.